THE ROLE OF WORK-LIFE BALANCE IN MEDIATING THE EFFECT OF WORK FROM HOME IMPLEMENTATION ON BURNOUT AND PSYCHOLOGICAL DISTRESS AMONG GENERATION Z OFFICE EMPLOYEES WITH WORKLOAD AS A MODERATING VARIABLE - Ni Made Widiyastiti; Nyoman Sri Subawa (RADJA PUBLIKA, 2026)
This study aims to examine the role of work-life balance in mediating the effect of work from home (WFH) implementation on burnout and psychological distress among Generation Z office employees, with workload as a moderating variable. The study was conducted in Indonesia and focused on Generation Z employees aged 18–28 years who work under a WFH system and experience high workloads. This research employed a quantitative approach using non-probability sampling, specifically purposive sampling. The sample size was determined using the Hair formula based on 25 indicators, resulting in a minimum of 175 respondents. Primary data were collected through a Google Form–based questionnaire using a six-point Likert scale. Data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach. The findings indicate that WFH has a significant negative effect on burnout and psychological distress, suggesting a protective effect on the mental health of Generation Z employees. Furthermore, work-life balance partially mediates the relationship between WFH and both burnout and psychological distress. Workload acts as a selective moderator, weakening the relationship between WFH and work-life balance and strengthening the relationship between work-life balance and burnout, while showing no significant moderating effect on other relationships. Overall, the results suggest that WFH can enhance the mental well-being of Generation Z employees through improved work-life balance, although these benefits may diminish when workloads become excessively high.